Effect of silane hydrolysis on the interfacial adhesion of carbon nanotubes/glass fiber fabric-reinforced multiscale composites. Issue 4 (February 2018) - Zeng, Shaohua; Shen, Mingxia; Duan, Pengpeng; Xue, Yijiao; Wang, Zhuying
Three types of multiwall carbon nanotubes (MCNTs)/glass fiber fabrics (MGf) were prepared by dispersing industrial-grade MCNTs onto commercial E-glass fiber fabrics (GFfs) through an ultrasonic-assisted impregnation deposition method. The multiscale MGf-reinforced composites were fabricated by the vacuum infusion process. The effect of γ-aminopropyltrimethoxysilane (APS) or APS hydrolysis on the MCNT dispersion and the interfacial bonding between MCNTs and glass fiber were investigated by Fourier transform infrared spectroscopy, field-emission scanning electron microscopy, energy dispersive X-ray spectroscopy and their flexural stiffness, respectively. The interfacial adhesion of MGf composites was evaluated by interlaminar shear strength (ILSS) and dynamic mechanical thermal analysis. The results indicated that MCNTs on the MGf surface could form an interpenetrating network and act as anchors to interlock glass fiber with epoxy. The initial storage modulus and glass transition temperature of the MGf composites clearly increased, while the first loss factor of the MGf composites decreased by 30.0–45.0% compared with that of the GFf composite. Whether or not APS was hydrolyzed, it helped the MCNTs disperse on the GFf surface by chemical bonds. The ILSS of the multiscale composite with APS-treated MCNTs was enhanced significantly, while that with hydrolyzed APS-treated MCNTs (MGf-h) had a slight increase. APS hydrolysis increased the flexural rigidity of the MGf-h.